2013
DOI: 10.1159/000348809
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Onset Endophthalmitis Caused by Alloiococcus otitidis following a Dexamethasone Intravitreal Implant

Abstract: Purpose: To report the first case of acute endophthalmitis caused by Alloiococcus otitidis after a dexamethasone intravitreal implant. Methods: A 74-year-old female was treated with intravitreal Ozurdex® in her left eye for central retinal vein occlusion (CRVO). Best-corrected visual acuity (BCVA) in the eye was 4/20. Intravitreal injection was uneventful. At 48 h after injection, she developed ocular pain and visual acuity had dropped to light perception. Endophthalmitis associated with intravitreal injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…In the past, A. otitidis has been considered a commensal of the external ear canal (Frank et al, 2003 ; Tano et al, 2008 ). However, consensus on the role of A. otitidis remains divided, as A. otitidis has been shown to have pathogenic traits including eliciting immune responses in vitro (Himi et al, 2000 ; Tarkkanen et al, 2000 ; Harimaya et al, 2005 , 2007a , b , 2009 ), invading intracellularly (Faden and Dryja, 1989 ) and having been identified as a pathogen in device related (Marchino et al, 2013 ) and chronic infection (Cakar et al, 2013 ). Utilizing culture-independent 16S rRNA sequencing, our department confirmed that A. otitidis and H. influenzae are the two most common bacteria demonstrated in children with OME and that the external ear canal may act as a reservoir for the middle ear (Chan et al, 2017 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, A. otitidis has been considered a commensal of the external ear canal (Frank et al, 2003 ; Tano et al, 2008 ). However, consensus on the role of A. otitidis remains divided, as A. otitidis has been shown to have pathogenic traits including eliciting immune responses in vitro (Himi et al, 2000 ; Tarkkanen et al, 2000 ; Harimaya et al, 2005 , 2007a , b , 2009 ), invading intracellularly (Faden and Dryja, 1989 ) and having been identified as a pathogen in device related (Marchino et al, 2013 ) and chronic infection (Cakar et al, 2013 ). Utilizing culture-independent 16S rRNA sequencing, our department confirmed that A. otitidis and H. influenzae are the two most common bacteria demonstrated in children with OME and that the external ear canal may act as a reservoir for the middle ear (Chan et al, 2017 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects were reported to be conjunctival hemorrhage, increase in the intraocular pressure and cataract formation. 1,9 Few authors reported relatively remarkable complications related to dexamethasone implant such as splitting or migration of the implant to the anterior chamber. 12,13 Fragmentation of Ozurdex after the injection is believed to be a fairly common situation and seems to be innocuous, without causing any alteration in the efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] To the best of our knowledge, there are only a few reports of endophthalmitis after Ozurdex implant injection; these cases were either defined as the adverse events in large studies without any detail on management 3,8 or published as case reports. 9,10 Intravitreal injection-associated endophthalmitis is not an uncommon situation. 11 However, we propose that endophthalmitis due to slow-releasing dexamethasone implant should be delineated from endophthalmitis associated with common intravitreal agents, such as antivascular endothelial growth factors, because of its pharmacological properties.…”
mentioning
confidence: 99%
“…There have been isolated reports of A. otitidis and T. otitidis as causative agents of diseases seemingly unrelated to otitis media. A. otitidis has been described as the causative agent in two case reports, where it was isolated from vitreous fluid of a patient with acute-onset endopthalmitis (Marchino et al, 2013) and from blood cultures in a young adult with endocarditis (Guler et al, 2015). Both infections are usually caused by the Gram positive cocci Streptococcus and Staphylococcus (Marchino et al, 2013;Guler et al, 2015); it is possible that the cause was misidentified as these reports do not provide any detail on how the isolates were identified as A. otitidis.…”
Section: Pathogenicity In Diseases Other Than Otitis Mediamentioning
confidence: 99%
“…A. otitidis has been described as the causative agent in two case reports, where it was isolated from vitreous fluid of a patient with acute-onset endopthalmitis (Marchino et al, 2013) and from blood cultures in a young adult with endocarditis (Guler et al, 2015). Both infections are usually caused by the Gram positive cocci Streptococcus and Staphylococcus (Marchino et al, 2013;Guler et al, 2015); it is possible that the cause was misidentified as these reports do not provide any detail on how the isolates were identified as A. otitidis. In the endocarditis case, the patient had chronic OME with perforation which had apparently been a problem since childhood, so it is possible that in long-term severe disease A. otitidis can opportunistically infect the bloodstream.…”
Section: Pathogenicity In Diseases Other Than Otitis Mediamentioning
confidence: 99%